Foundationalist or Fallibilist: the epistemological ambiguity of Kant's theory and an answer against fallibilist oppositions to Kant - Vollet, Lucas Ribeiro (Studia Kantiana, 2017)
The following article argues for four main points: 1. Kant's epistemological thesis about the possibility of synthetic a priori judgments is neither a fallibilist nor a fundationalist stance on the nature of knowledge. 2. The inevitable epistemological ambiguity between fallibilism and foundationalism follows from a) Kant's in-between metaphysical thesis that mixes empirical realism and transcendental idealism, b) Kant's blended empiricism, that demands formal elements of subjectivity in order to authorize possible experience and c) the creation of an "in-between" rhetoric that allows Kant to (c.1) transit between the best features of seemingly opposite philosophies, and (c.2) allows him to preserve his set of problems from being kidnapped by technical approaches or empirical science methodologies 3. Kant's answer to the question of knowledge and empirical validity only acquires meaning inside the rhetorical structure of a transcendental problem that involves the linking of the problem of knowledge (and empirical validity) to the practical-human problem and its post-metaphysical residues. 4.The impossibility to place Kant in one or another side of the debate between fallibilists and foundationalists (being the same valid for the conflict between realists and idealists) shows an incorrigible limitation to the fallibilist and naturalist critiques of the a priori formal theory of Kant.